Association between HLA-DRB1* allele polymorphism and caries susceptibility in Han Chinese children and adolescents in the Xinjiang Uygur Autonomous Region - Wang, Liping (J Int Med Res, 2019)
OBJECTIVE: The rate of caries and the mean number of decayed, missing, or filled teeth were reported to be significantly higher in children in the Xinjiang Uygur Autonomous Region than in children in eastern China. Little is known regarding the genetic basis of caries among residents of the Xinjiang Uygur Autonomous Region. This study investigated the association between HLA-DRB1 alleles and caries susceptibility in Han Chinese children and adolescents in the Xinjiang Uygur Autonomous Region. METHODS: HLA-DRB1 allele frequency was assessed in DNA samples from buccal swabs of 42 patients with caries and 123 healthy control participants using a polymerase chain reaction method with sequence-specific primers. The chi-squared test or Fisher’s exact test, followed by Bonferroni correction, was used to calculate differences in allele frequencies between groups. RESULTS: Compared with the healthy controls, the allele frequency of HLA-DRB1*13 was significantly higher in patients with caries in the Xinjiang Uygur Autonomous Region (35.71% vs. 18.70%). The allele frequency of HLA-DRB1*09 was significantly lower in patients with caries than in healthy controls (4.76% vs. 25.20%). CONCLUSIONS: HLA-DRB1*13 alleles could confer greater caries susceptibility, whereas HLA-DRB1*09 could be protective against caries pathogenesis, in Han Chinese children in the Xinjiang Uygur Autonomous Region.